Publicism of Maxim Tank in the Western Belarusian period: genre and thematic dominants - Tychko, Halina K. (Journal of the Belarusian State University. Journalism, 2025)
The necessity of updating the research of the phenomenon of Western Belarusian periodicals is substantiated using the example of the analysis of the publicistic heritage of Maxim Tank. The history of the Western Belarusian press in 1929–1939 is considered. Based on the analysis of Maxim Tank’s publicistic materials, the thematic and genre features of the texts are determined. The influence of the historical context on the aesthetic and value-moral dominants of the periodical press of that time is analysed. The reasons for contradictory approaches to the assessment of works of art are considered. Conclusions are made about the priority role of the author’s civic position in journalistic publications.
Keywords: Western Belarusian periodicals; publicistic texts; genres of artistic publicism; historical context; civic position